Biomechanical testing of different fixation techniques for intraoperative proximal femur fractures: a technical note. Issue 1 (31st December 2022) - Wendler, Toni; Fischer, Benjamin; Brand, Alexander; Weidling, Martin; Fakler, Johannes; Zajonz, Dirk; Osterhoff, Georg
ABSTRACT: Intraoperative proximal femoral fractures (IPFF) represent a rare but challenging complication of total hip arthroplasties. They usually occur as a longitudinal split. This pilot trial aimed to compare the biomechanical primary stability of different fixation techniques for IPFF. Standardised longitudinal medial split fractures of the proximal femur (type II, Modified Mallory Classification) were created in artificial osteoporotic and non-osteoporotic composite femora after implantation of a cementless femoral stem. Five different fixation techniques were compared: cerclage band, cerclage wiring with one or two wires, and lag screw fixation with one or two lag screws. A quasi-static loading protocol was applied and failure loads were evaluated. The observed median failure loads were 4192N (3982N – 5189N) for one cerclage band, 4450N (3577N – 4927N) for one cerclage wire, 5016N (4175N – 5685N) for two cerclage wires, 6085N (5000N – 8907N) for one lag screw, and 4774N (4509N – 8502N) for two lag screws. Due to the wide range of failure loads within the experimental groups, there were no observable differences between the groups. All fixation techniques provided sufficient primary stability in osteoporotic and non-osteoporotic composite bones. Further cadaveric studies with larger sample sizes may be needed to confirm the results presented here.